COMPARISON between COVID-19 and MERS demographic data in Saudi Arabia: a retrospective study. Issue 1 (1st January 2021) - Mohamed, Rania Ali El Hadi; Abdullah Thagfan, Felwa
ABSTRACT: The outbreak of corona virus disease (COVID-19) caused by the new severe acute respiratory syndrome corona virus 2 began in Wuhan, China, resulting in respiratory disorders. In January of 2020, the World Health Organization declared the outbreak a pandemic owing to its global spread. Because no studies have investigated COVID-19 in Saudi Arabia, this study investigated similarities and differences between demographic data during the COVID-19 and Middle East respiratory syndrome (MERS) outbreaks in Saudi Arabia. A retrospective trend analysis was performed to assess demographic data of all laboratory-confirmed MERS and COVID-19 cases. Patients' charts were reviewed for data on demographics, mortality, citizenship, sex ratio, and age groups with descriptive and comparative statistics; the data were analyzed using a non-parametric binomial test and chi-square test. Of all COVID-19 patients in Saudi Arabia, 78%were male patients and 22% were female patients. This proportion of male COVID-19 patients was similar to that of male MERS patients, which also affected male patients more frequently than female patients. The number of COVID-19-positive Saudi cases was lower than that of non-Saudi cases, which were in contrast to that of MERS; COVID-19 appeared to be remarkably similar to MERS with respect to recovered cases. However, the numbers of critical and dead COVID-19 patients have been much lower than those of MERS patients. The largest proportion of COVID-19 and MERS cases (44.05% and 40.8%, respectively) were recorded in the Western region. MERS and COVID-19 exhibited similar threats to the lives of adults and the elderly, despite lower mortality rates during the COVID-19 epidemic. Targeted prevention of and interventions against MERS should be allocated populations according to the areas where they inhabit. However, much more information regarding the dynamics and epidemiology of COVID-19 in Saudi Arabia is needed. Abbrevation : MERS: Middle East Respiratory syndrome; COVID-19: Corona Virus Disease 2019.